REVOLUSI ILMIAH THOMAS KUHN DAN RELEVANSINYA TERHADAP PENGEMBANGAN DAN PEMBAHARUAN ILMU NAHW - Afif Kholisun Nashoih (JURNAL PUSAKA, 2019)
Thomas Kuhn's idea of ??the scientific revolution contained in his magnum opus has become a new face in the development and birth of science. It starts from normal science that experiences anomalies and raises crises, so it needs to be attempted for the occurrence of shifting paradigm, by shifting the old paradigm with a new paradigm, which eventually gives birth to a scientific revolution. This Kuhn thought has relevance to various fields, such as nahw. Nahw as the grammatical Arabic language contains philosophical elements, which make it a complex language. In this context, nahw as a normal science cannot overcome the existing problems, so a crisis is born. The crisis received attention by several Arabic language experts, such as Ibn Madl?`, Syauq? Dlaif, and Tam?m Hasan. They assumed there is one factor that makes nahw complicated, namely the concept of ‘?mil. Therefore, for them, nahw needs to be reconstructed and renewed. Construction of nahw with new faces contained in each magnum opus, Ibn Madl?` in his book "Kit?b al-Radd ‘al? al-Nuh?t", Syauq? Dlaif in "Tajd?d al-Nahw ", and Tam?m Hasan in "al-‘Arabiyyah: Ma'n?h? wa Mabn?h?". In all three books, nahw experienced a great revolution.